Research on the electrochemical performance of polyoxovanadate material K4Na2V10O28 as a novel aqueous zinc-ion batteries cathode. (20th August 2022) - Zhou, Tao; Xiao, Haoran; Xie, Lingling; Han, Qing; Qiu, Xuejing; Xiao, Yongmei; Yang, Xinli; Zhu, Limin; Cao, Xiaoyu
Abstract: The aqueous zinc-ion batteries (ZIBs) field has witnessed a tremendous advancement in the exploration of materials that can combine high energy density and short charge times. Nevertheless, these materials are primarily focused on manganese-based or vanadium-based oxides, and there are fewer reports on new materials. Herein, we proposed a new ZIBs cathode material based on polyoxovanadates (POVs) type K4 Na2 V10 O28 (KNVO). It demonstrated the advantages of POVs, which could undergo multi-electron redox processes at each V center. The reversible capacity was maintained at 152.3 mAh g −1 after 100 cycles at 0.1 A g −1, and the capacity retention was close to 100% after 1000 cycles at 1 A g −1 . Additionally, the kinetic properties of the KNVO/Zn cell were investigated by Trasatti research, pseudocapacitance analysis and GITT test, respectively, manifesting a strong capacitive behavior as well as a high Zn 2+ diffusion coefficient (order of 10 −10 cm 2 s −1 ). Not only that, but we also analyzed the relevant characteristic parameters of EIS in-depth, aiming to systematically probe the changes in electrochemical behavior before and after cycling. The synthesis and investigation of KNVO cathode materials may provide directions for the development of electrode materials for a rising generation of aqueous ZIBs.